Mangrove-Based Dodol Innovation and Coastal Household Economic Resilience: Evidence From A Quasi-Experimental Study. - Harahap, Kurnia Sada; Martini, Martini; Aulia, Deni; Maskur, Muhammad (Faculty of Fisheries and Marine Science, Brawijaya University, 2026)
This study examines the association between the adoption of mangrove-based dodol (a traditional Indonesian chewy confection) innovation and changes in economic resilience among members of the Wilmar Employees’ Wives Association (IIKW) in Dumai City, Riau Province. A quasi-experimental design combining Propensity Score Matching (PSM) and Difference-in-Differences (DID) was applied to 50 households (25 adopters and 25 non-adopters) observed before the intervention in 2021 and after the intervention in 2024. PSM was used to improve baseline comparability, while DID estimated differential changes between groups over time. After matching, the mean standardized bias decreased from 13.9% to 3.5%, and post-matching covariates were statistically balanced. The estimated DID effects were positive for monthly household income (+IDR 1.10 million; p = 0.011), income-source diversification (+1.02 sources; p = 0.034), savings share (+5.9 percentage points; p = 0.030), productive assets (+IDR 5.2 million; p = 0.016), and the Economic Resilience Index (ERI) (+0.15; p = 0.012), while the food-expenditure share declined by 7.0 percentage points (p = 0.026). These estimates suggest that mangrove-based dodol adoption was associated with improved economic resilience within the matched study population. However, the small sample limits statistical power, sensitivity to outliers, and external validity; therefore, the findings should be interpreted as localized evidence rather than population-wide effects.